Autonomic Neuropathy in Diabetes Mellitus - Verrotti, Alberto; Prezioso, Giovanni; Scattoni, Raffaella; Chiarelli, Francesco (Frontiers in Endocrinology, 2014)
Diabetic autonomic neuropathy (DAN) is a serious and common complication of diabetes, often overlooked and misdiagnosed. It is a systemic-wide disorder that may be asymptomatic in the early stages. The most studied and clinically important form of DAN is cardiovascular autonomic neuropathy (CAN) defined as the impairment of autonomic control of the cardiovascular system in patients with diabetes after exclusion of other causes. The reported prevalence of DAN varies widely depending on inconsistent definition, different diagnostic method, different patient cohorts studied. The pathogenesis is still unclear and probably multifactorial. Once DAN becomes clinically evident, no form of therapy has been identified which can effectively stop or reverse it. Prevention strategies are based on strict glycemic control with intensive insulin treatment, multifactorial intervention and lifestyle modification including control of hypertension, dyslipidemia, stop smoking, weight loss and adequate physical exercise. The present review summarizes the latest knowledge regarding clinical presentation, epidemiology, pathogenesis and management of DAN, with some mention to childhood and adolescent population.